2008
DOI: 10.2186/prp.7.97
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Changes in Swallowing Function Caused by a Palate Covering

Abstract: Use of prostheses such as complete dentures is often avoided in dysphagia rehabilitation for the elderly due to the effects of the palate covering. However, the influence of the palate covering is relieved over a short time (approximately 7 days), suggesting that the commonly used approach should be reconsidered. AbstractPurpose: The purpose of this study was to elucidate the temporal relationship between habituation to a palate covered by a prosthesis and swallowing function. Materials and methods: Ten health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Prosthodontic treatment success depends on patients' ability to adapt to an altered oral environment that contains removable prostheses . Covering the palate with removable dentures is essentially uncomfortable for patients, and they have difficulty habituating to using such dentures , although maxillary dentures often cover the palate to obtain adequate denture retention and stability . Behavioural studies have shown that palatal coverage impaired masticatory performance and bolus formation and that adaptive changes occurred in 1 week.…”
Section: Introductionmentioning
confidence: 99%
“…Prosthodontic treatment success depends on patients' ability to adapt to an altered oral environment that contains removable prostheses . Covering the palate with removable dentures is essentially uncomfortable for patients, and they have difficulty habituating to using such dentures , although maxillary dentures often cover the palate to obtain adequate denture retention and stability . Behavioural studies have shown that palatal coverage impaired masticatory performance and bolus formation and that adaptive changes occurred in 1 week.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods, including electromyography, ultrasonography, videofluorography and pressure sensor measurement, have been used to evaluate the tongue function. In particular, evaluation of tongue pressure with a pressure sensor allows non‐invasive collection of accurate quantitative data on the time and force related to swallowing (12–17). Miller et al.…”
Section: Introductionmentioning
confidence: 99%
“…In general, about 1 week may be required to become accustomed to palatal coverage . In the present study, measurements were taken for 2 weeks as a preliminary experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, subjects learned to increase the number of mastication strokes to form an easy swallowable bolus, compensating for reduced masticatory performance by palatal coverage. A possible explanation of reductions in BFI and DE is that wearing the plate blocked palate sensation (18) and altered the anatomical shape of the oral cavity, impairing the tongue movement during mastication (6,7). After wearing the palatal plate, only tongue sensations could be used to determine whether a swallowable bolus had been formed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation